Slovenian national survey of sexual lifestyles, attitudes and health - Klavs, Irena (Zdravstveno varstvo, 2006)
Introduction: A national survey of sexual lifestyles, attitudes and health in Slovene men and women aged 18 to 49 years was conducted. This paper reports onthe preparatory work and feasibility study. Methods: The feasibility study used a stratified two-stage probability design for the selection of the samplefrom the Central Population Registry. Data were collected between 1996 and 1997. A combination of face-to-face interviews and anonymously self-administered questionnaires was used. Results: The overall response rate was 77.4 %. Two percent of respondents reported having had ten or more heterosexual partners during the five years preceding the interview, and 14 °lduring their lifetime. Slightly more then 2 °l of male respondents reported having ever paid a woman for sex, and less than 0.5 ` admitted to having had homosexual sex during the past five years. The problem identified in the performance of the self-administered questionnaire was that many respondents omitted their current steady partner from the total count of partners for different periods. Conclusions: The high overall response rate indicated that good acceptability could be expected for the main survey. The self-administered questionnaire was divided into four booklets in order to provide opportunity for a brief introduction before giving them to respondents. It was decided to change the order of questions asking about the number of partners during different periods, and to start with questions for the most recent period, last month, and then to proceed with questions for thelast year, last five years and lifetime. The results helped us design the main survey conducted in 1999 and 2001.
Keywords: ankete; Feasibility Studies; Hiv; Izvedljivost , študije; Questionnaires; Sex Behavior; sexual intercourse; Sexually Transmitted Diseases; Spolno prenosljive bolezni; Spolno vedenje; spolnost